US Invasion in Afghanistan and Its Impact on Women’s Political Rights: https://doi.org/10.55966/assaj.2025.4.1.095 - Mr. Tariq; Pro. Dr. Fauzia Ghani (`, 2025)
This research article assesses the impact of US military intervention beside of reconstruction exposure of the political‑rights status of Afghan women. Based on a cross-sectional survey of 200 women (age 18-60) in urban (Kabul, Herat) and rural (Nangarhar, Balkh) provinces, my research measures three dimensions of political rights: knowledge of legal guarantees (constitutional provisions and gender‑quota laws), electoral participation (voting behavior and candidacy aspirations), and involvement in community governance structures. A proxy of exposure was used as the main predictor; the number of years lived within a certain distance of U.S. bases or projects (exposure index). Data were analyzed statistically (descriptive statistics, reliability analysis, the one-way analysis of variance (AVOVA) which is followed by Tukey Post-hoc test considering the independent variable‑samples t‑test. SPSS is used combined by correlation Coefficients Pearson and hierarchical regression analysis multiple. Findings show that higher levels of indirect exposure to U.S. presence are substantially related to higher scores on all three political‑rights facets (β = 0.41 for legal level of awareness, p <. 001), and urban women had better results than rural ones. These results indicate that international interventions are similar to building women’s political power when combined with secure environments and rights‑education projects. Implications include the importance of equal outreach to rural areas and the importance of a test of time evaluation to monitor longer term benefits. Keywords: U.S. intervention; Afghanistan; women’s political rights; survey research; SPSS; legal awareness; electoral engagement.